The governance role and activity in colleges of further education - Lee, Beverley (2000)
This thesis examines the role of the board of governors in colleges of further education (FE). Despite being a significant area of activity, comprising over 440 colleges, which were allocated a total of three billion pounds of public money in 1998, FE remains a notably under-researched sector. This thesis contributes to the knowledge and understanding of the governance activity in the sector by going beyond demographic data and using a case approach to examine the nature of the work undertaken by the board. This work is also important because it is able to utilise data gathered from observations of a college board as it undertakes its work.